The Effect of Parent-Assisted Reading Intervention Program _x000D_ on Second Grade Students’ Fluent Reading and Reading _x000D_ Comprehension Skills - DOĞAN, MİDRABİ CİHANGİR (My University, 2021)
In this study, Parent-Assisted Reading Intervention Program was developed and its effects were examined on students’ fluent reading and reading comprehension skills. The research was conducted in the context of the randomized pretestposttest control group design adapted from one of the true experimental design models. The study group included 16 students from the second grade: eight students in an experimental group and eight in a control group. Criterion sampling and simple random sampling were used to establish the study groups. In the research, curriculum-based measurement, error analysis inventory, prosodic reading scale, and reading comprehension tests were used as data collection tools. In the study, the Mann-Whitney U test, which is one of the nonparametric tests, was used to compare the pretest-posttest scores of the two groups. Further, the Wilcoxon signed-rank test was used to compare the pretest-posttest scores of each group. From the results of this study, it was concluded that the Parent-Assisted Reading Intervention Program was effective in improving the fluent reading and reading comprehension skills of the students involved.